فاعلية استخدام خرائط التفكير في اكتساب المفاهيم التاريخية لدى طالبات الصف السابع الاساسي في مادة العلوم الاجتماعية - حسين, أ.د.جواد نعمت; سعيد, سولاف زياد (Sulaimani Journal for Humanities, 2023)
The research aims to investigate the impact of thinking maps strategy on the acquisition of historical concepts among seventh grade students. The researcher used the experimental approach due to its suitability to the nature of the research problem. The research community consisted of (90) students in the seventh grade in the primary stage (chawas) for the academic year (2022-2023). Using the arithmetic mean, standard deviation, percentage, Pearson's correlation coefficient and t-test for two independent samples, the researcher concluded the following: - The students of the experimental group, who study according to the strategy of thinking maps, excelled in the test of acquiring historical concepts over the students of the control group, which study according to the traditional method used in teaching. The study recommended writing social studies books and paying attention to the thinking maps strategy, giving courses to teachers of history and social sciences and training them to use the thinking maps strategy in teaching.
Keywords: thinking maps; historical concepts